Analisis Tingkat Penerapan Good Coorporate Governance Pada Usaha Kecil dan Menengah di Kota Medan - Juliana Nasution; Hanifah Oktaviani Fakhri; Riski Sobari; Andi Hotmatua Harahap (LPPM Universitas Labuhanbatu, 2024)
In Indonesia this millennium there have been many established companies and companies, especially in the city of Medan, and companies face stiff competition, even if it is a certain type of company, so that there is often a risk of company bankruptcy. innovative, creative and predictable ideas, the current implementation of good corporate governance (GCG) is highly recommended. Because of this, GCG is becoming more and more popular. Not only popular, but also plays an important role as a reference for the company's image. This research approach is descriptive qualitative research. Once the required information is available, the information is grouped and described based on the nature of the information. This type of data is then analyzed using descriptive methods, namely analyzing theory and connecting it to the problem under study. Factors influencing the implementation of GCG in Medan City for UKM include UKM awareness of the importance of GCG implementation, government regulations regarding GCG implementation, knowledge and skills of UKM regarding GCG implementation and access to finance and other resources needed for GCG implementation. At the same time, the government also requires government regulations designed to implement GCG to ensure compliance. Therefore, this problem can be studied in different ways and with different approaches. A literature study to analyze the level of GCG implementation in small and medium enterprises in Medan City is proposed to investigate various aspects related to GCG.